“A ROADMAP FOR THE IMPLEMENTATION OF DIGITAL TECHNOLOGIES TO IMPROVE THE QUALITY OF TEACHING IN EDUCATIONAL INSTITUTIONS AND THE EVALUATION OF ITS EFFECTIVENESS” - To‘xtamisheva Dilrabo Shermonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The aim of the study is to develop a strategy for improving the quality of teaching through the implementation of digital technologies in the educational process and to evaluate its effectiveness. The research methods include literature analysis, surveys and expert assessment, as well as the measurement of effectiveness based on statistical indicators. As a result, a roadmap for the integration of digital technologies has been developed, and criteria for evaluating its effectiveness have been identified. The findings of the study are intended to be used as practical recommendations for enhancing the quality of education.